Rotemberg and Imperfect Common Knowledge: A Solution Algorithm - Radek Šauer (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper develops an algorithm that enables to solve macroeconomic models with Rotemberg pricing and imperfect common knowledge. Under the concept of imperfect common knowledge, Rotemberg pricing requires the solution algorithm to take prices explicitly into account. The state space includes the hierarchy of average higher-order expectations as well as the aggregate price level. In addition to determining the usual policy functions of output, inflation, and the nominal interest rate, the algorithm has to search for the policy function of the aggregate price and for the policy function of the firm-specific price.
Keywords: C63; D82; E31; 330; Rotemberg pricing; dispersed information; heterogenous beliefs; Kalman filter; higher-order expectations